The Influence of Drug Prices and Service Quality on Customer Satisfaction at Fahry Farma Pharmacy Bangkalan - Teguh Setiawan Wibowo; Reni Oktavia Saputri; Dwi Bhakti Iriantini (Jurnal Ekonomi dan Bisnis Digital, 2023)
Pharmacies are places where pharmaceutical work is carried out and have an important role as a place to obtain information about drugs. The research design used in this study is the study’s normality, validity, and reliability test using SPSS version 26.0 with valid and reliable status. The methods used are multiple linear regression, correlation coefficient, determination coefficient, T-test, and F-test. random sampling technique, data collection using research instruments, and quantitative or statistical data analysis to test the established hypothesis. Based on the results of the tests that have been carried out, there is an influence between the independent variables, namely service quality and price, and the dependent variable, namely satisfaction, based on the T-test and F-test. The results of the T-test are T arithmetic > t table and a significance value < alpha 0.05, while the F-test has F arithmetic > f table and a significance value < alpha 0.05.